Thermal Measurement and its Application for Diagnostics of Distribution Oil Transformers - D. Korenciak; M. Sebok; M. Gutten (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In the first part of the paper the theory of infrared radiation and the use of nondestructive measurement of electrical devices by means of thermovision are under analysis. In the second part of paper basic principles and application of non-contact temperature measurement are examined. In the third part of paper thermal processes in distribution oil transformer – temperature in dependence on height of oil transformer and temperature distribution in sectional plan of oil transformer – are considered. In the fourth part of paper, by means of the experimental measurements and subsequent analysis, practical thermal imaging and contact thermal measurements by optical detectors for the diagnosis of distribution oil transformers in the field of mechanical strength of windings are shown. In this paper, we wanted to show out the possibility of using thermal measurements in this field of analysis and detection of quality of winding for distribution oil transformer. It is possible to use these methods to localize places of faults, and they are also applicable for the diagnosis and detection of disorders of the quality of materials and other anomalies during operation of the equipment. By means of the experimental measurements followed by diagnostic analysis the practical use of thermovision and optical sensors for diagnostics of power oil transformers in field mechanical strength and quality of winding is demonstrated.